Pengaruh Full Day School Dan Pemanfaatan Perpustakaan Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi Fase E Di SMA Negeri 8 Padang - Detman; Widya Astuti; Widya Sulastri (JURNAL ARMADA PENDIDIKAN, 2025)
This study aims to examine: (1) the influence of full day school on student learning outcomes in economics subject phase E at SMA Negeri 8 Padang, (2) the influence of library utilization on student learning outcomes, and (3) the simultaneous influence of full day school and library utilization on learning outcomes. This research applies a quantitative approach with a sample of 188 students selected through proportional random sampling from a population of 356 students. Data were collected using a questionnaire and analyzed through multiple linear regression assisted by SPSS Version 27. The hypothesis was tested using the t-test and F-test. The results indicate that full day school has a positive and significant effect on student learning outcomes, with t_count value of 4.802 > t_table 1.972 with a significance value of 0.000 < 0.05. Similarly, library utilization shows a positive and significant effect, with t_count = 3.106 > t_table 1.972 with a significance value of 0.002 < 0.05. Simultaneously, full day school and library utilization influence learning outcomes with F_count value of 78.261 > F_table 3.143 with a significance level of 0.000 < 0.05. Based on the results of the study, it was concluded that full day school and library utilization have a positive and significant effect on student learning outcomes in economics phase E at SMA Negeri 8 Padang.